Investigation of Multifrequency Piezoelectric Energy Harvester - Andrius Čeponis; Dalius Mažeika (Shock and Vibration)
This paper presents results of numerical and experimental investigations related to the piezoelectric energy harvester that operates at multifrequency mode. Employment of such operation principle provides an opportunity for obtaining frequency response characteristics of the harvester with several resonant frequencies and in this way increasing efficiency of the harvester at a wide spectrum of excitation frequencies. The proposed design of the energy harvester consists of five cantilevers which forms square type system. Cross sections of the cantilevers are modified by periodical cylindrical gaps in order to increase strain value and to obtain more uniform strain distribution along the cantilevers. Cantilevers are rigidly connected to each other and compose an indissoluble system. Square type harvester has seismic masses at every corner. These masses are placed under specific angle in order to reduce natural frequencies of the system and to create additional rotation moments in the body of harvester. Results of the numerical investigation revealed that harvester has five resonance frequencies in the range from 15 Hz to 300 Hz. Numerical analysis of the harvester revealed that the highest open circuit voltage density is 19.85 mV/mm3. Moreover, density of the total electrical energy reached 27.5 μJ/mm3. Experimental investigation confirmed that frequency response characteristics are obtained during numerical investigation and showed that energy density of the whole system reached 30.8 μJ/mm3.